2018
DOI: 10.1016/j.oooo.2017.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Transient bacteremia induced by dental cleaning is not associated with infection of central venous catheters in patients with cancer

Abstract: Bacteremia resulting from dental cleaning is transient and unlikely to cause CVC-related infection or BSI in patients with absolute neutrophil count greater than 1000 cells/µL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…2931 A study published in 2018, which evaluated human patients with central venous catheter placement as a result of an oncological medical condition, yielded no evidence of persistent bacteremia at 30-min and 24-h post-dental cleaning. 32 Transient bacteremia is also known to be short lived in healthy individuals, as much of the bacteremia can be eliminated by the host immune response alone. Recently, a study performed on equines with dental extractions explored bacteremia in the absence of antimicrobial administration, 33 but similar studies have not been conducted in companion animals.…”
Section: Introductionmentioning
confidence: 99%
“…2931 A study published in 2018, which evaluated human patients with central venous catheter placement as a result of an oncological medical condition, yielded no evidence of persistent bacteremia at 30-min and 24-h post-dental cleaning. 32 Transient bacteremia is also known to be short lived in healthy individuals, as much of the bacteremia can be eliminated by the host immune response alone. Recently, a study performed on equines with dental extractions explored bacteremia in the absence of antimicrobial administration, 33 but similar studies have not been conducted in companion animals.…”
Section: Introductionmentioning
confidence: 99%
“…A balance of benefits and harms must be considered in determining the usefulness of any medical treatment. There have been four reports 18–21 on the harms of dental treatment during cancer therapy, particularly regarding the treatment of periodontal disease (i.e., tooth brushing, calculus scaling, and periodontal surgery) or tooth extraction (Table 5). According to a study by Weikel et al 18 on periodontal therapy comparing fever and bacteremia in cancer patients with and without invasive periodontal therapy in the presence of myelosuppression, no significant difference was observed between the two groups.…”
Section: Harm Caused By Dental Treatment In Cancer Carementioning
confidence: 99%
“…However, approximately half of the patients in both groups had less than 500 μL neutrophils and received prophylactic antimicrobial therapy. In addition, Usmani et al 19 reported that cancer patients treated with subgingival calculus scaling (all with more than 1000 μL neutrophils and no prophylactic antimicrobial therapy) had bacteremia immediately after the procedure; however, the presence of bacteria was temporary with no life‐threatening systemic infection. On the other hand, a study by Raut et al 20 compared patients who had tooth extraction before hematological cancer treatment with those who did not and found that the incidence of complications from tooth extraction was high (13%).…”
Section: Harm Caused By Dental Treatment In Cancer Carementioning
confidence: 99%